Interpersonal Comunication Model of Teacher in Development Self Relliance of Deaf Students Outside School of the Pembina Aceh Tamiang - Mulyana, Afriani Eka; Lubis, Suwardi; Kholil, Syukur (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The learning process at the State School of Builders located in Aceh Tamiang, interpersonal communication is more intense between teachers and students, because one of the learning methods for students with special needs is individualised learning. Purpose. This research aims to analyze how the teacher’s interpersonal communication model develops self relliance for junior high school deaf students at the Pembina Aceh Tamiang State Special School.Not only that, what communication barriers occur and efforts to overcome these communication barriers. Researchers use the interpersonal communication model and symbolic interaction theory from George Herbert Mead. Method. This research uses descriptive research methods with a qualitative approach, with research subjects consisting of 4 middle school level teachers who are deaf. Data collection techniques were semi-structured interviews, passive participant observation, and documentation. Data analysis uses Miles, Huberman and Saldana theoretical techniques, namely data collection, data condensation, data presentation, and conclusion drawing/verification. The data validity technique that researchers use is source triangulation. Results. The results showed that the teacher’s interpersonal communication model in developing students’ self reliance at the Aceh Taming Pembina State Special School uses non-verbal and verbal communication. However, teachers often use non-verbal communication because of students’ limitations in hearing, making teachers and deaf students when interacting more dominantly use non-verbal communication. The effectiveness of teachers’ interpersonal communication with deaf students can be seen through 4 aspects, namely openness, empathy, supportive attitude, and positive attitude. There are 4 factors inhibiting teachers’ interpersonal communication with deaf students in improving the independence attitude of deaf students, namely: physical interference, physiological interference, psychological interference, and semantic interference. Conclusion. The conclusion of this research is that the teacher’s interpersonal communication model in developing student independence at the Tamiang Aceh Pembina State Special School uses non-verbal and verbal forms of communication. The meaning of verbal communication for tunagrahita is a sentence or utterance spoken from the mouth, or called a mouth mimic, while the nonverbal communication they use is called sign language or symbol language.